Design and synthesis of novel pyrimidine analogs as highly selective, non-covalent BTK inhibitors. Issue 2 (15th January 2018) - Kawahata, Wataru; Asami, Tokiko; Irie, Takayuki; Sawa, Masaaki
Graphical abstract: Abstract: BTK is a promising target for the treatment of multiple diseases such as B cell malignances, asthma, and rheumatoid arthritis. Here, we report the discovery of a series of novel pyrimidine analogs as potent, highly selective, non-covalent inhibitors of BTK. Compound25d demonstrated higher affinity to an unactivated conformation of BTK that resulted in an excellent kinase selectivity. Compound25d showed a good oral bioavailability in mice, and significantly inhibits the PCA reaction in mice.